2001
DOI: 10.1074/jbc.m009144200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C α-mediated Negative Feedback Regulation Is Responsible for the Termination of Insulin-like Growth Factor I-induced Activation of Nuclear Phospholipase C β1 in Swiss 3T3 Cells

Abstract: Previous studies from several independent laboratories have demonstrated the existence of an autonomous phosphoinositide (PI) cycle within the nucleus, where it is involved in both cell proliferation and differentiation. Stimulation of Swiss 3T3 cells with insulin-like growth factor-I (IGF-I) has been shown to induce a transient and rapid increase in the activity of nuclear-localized phospholipase C (PLC) ␤1, which in turn leads to the production of inositol trisphosphate and diacylglycerol in the nucleus. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 53 publications
2
36
1
Order By: Relevance
“…12,13 Indeed, we demonstrated that upregulation of both the isoforms of PLCβ1 correlated with the activation of G 1 -specific cyclin D3/cdk4 complex, leading cells to an increased progression through G 1 phase. 11 Further evidence about PLCβ1 involvement in cell cycle control was reported again in FELC; in fact, it has been shown that PLCβ1 was involved in lamin B1 phosphorylation and G 2 /M progression via PKCα activation in the nucleus. 12 The direct target of PLC signaling is represented by protein kinases C (PKC), which are activated by the second messengers DAG and IP3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Indeed, we demonstrated that upregulation of both the isoforms of PLCβ1 correlated with the activation of G 1 -specific cyclin D3/cdk4 complex, leading cells to an increased progression through G 1 phase. 11 Further evidence about PLCβ1 involvement in cell cycle control was reported again in FELC; in fact, it has been shown that PLCβ1 was involved in lamin B1 phosphorylation and G 2 /M progression via PKCα activation in the nucleus. 12 The direct target of PLC signaling is represented by protein kinases C (PKC), which are activated by the second messengers DAG and IP3.…”
Section: Introductionmentioning
confidence: 99%
“…strengthened by the finding that its overexpression was sufficient to drive Swiss 3T3 in S phase of the cell cycle. 11 Subsequent studies on Friend murine erythroleukemia cells (FELC) showed a role for PLCβ1 in cell cycle control in both G 0 -G 1 /S transition and G 2 /M progression. 12,13 Indeed, we demonstrated that upregulation of both the isoforms of PLCβ1 correlated with the activation of G 1 -specific cyclin D3/cdk4 complex, leading cells to an increased progression through G 1 phase.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, rat adipocytes were pulse-labeled with [ 35 S]methionine and [ 35 S]cysteine for 2 h and then chased in a "cold" medium for different time periods. Cell lysates and culture medium were collected and subjected to immunoprecipitation using the anti-mouse adiponectin antibody as we previously described (28). A non-heating and non-reducing SDS-PAGE analysis revealed that all the three oligomeric complexes of adiponectin were immunoprecipitated by the rabbit anti adiponectin IgG (Fig.…”
Section: Figmentioning
confidence: 99%
“…PKC confers negative feedback regulation of IGF-1 signaling, terminating activation of nuclear PLC-β 1 by IGF-1 (43). Overexpression of either a PLC-β 1 mutant, in which the Ser 887 was replaced by Ala or a dominant negative PKCα, resulted in a sustained activation of nuclear PLC-β 1 following IGF-1 stimulation.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…GPCR stimulation of PLC-β generates diacylglycerol, which activates PKC. PKC phosphorylates PLC-β 1 in vivo and in vitro at Ser 887 (18,42,43). Both the convention and novel PKC isoforms phosphorylate PLC-β 1 .…”
Section: Protein Kinasesmentioning
confidence: 99%